2016
DOI: 10.1111/ctr.12741
|View full text |Cite
|
Sign up to set email alerts
|

A rare complication after allogeneic stem cell transplantation: post‐transplant erythrocytosis

Abstract: Post-transplant erythrocytosis is an infrequent complication and has been reported after allogeneic hematopoietic stem cell transplantation (allo-HSCT) in aplastic anemia, acute myeloid leukemia, and chronic myeloid leukemia. The pre-disposing factors and treatment are not clearly defined. We present 11 post-transplant erythrocytosis cases. More studies should be conducted to distinguish the pathogenesis and follow-up for this rare complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The incidence of post‐renal transplant erythrocytosis is between 5% and 20% and is decreasing (Kiberd, ). PTE also occurs in approximately 1% of patients after haematopoetic stem cell transplantation (HSCT) (Ahmed et al , ; Atilla et al , ) and after combined pancreatic–renal transplant, with a reported incidence of 16% (Guerra et al , ).…”
Section: Management Of Secondary Erythrocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of post‐renal transplant erythrocytosis is between 5% and 20% and is decreasing (Kiberd, ). PTE also occurs in approximately 1% of patients after haematopoetic stem cell transplantation (HSCT) (Ahmed et al , ; Atilla et al , ) and after combined pancreatic–renal transplant, with a reported incidence of 16% (Guerra et al , ).…”
Section: Management Of Secondary Erythrocytosismentioning
confidence: 99%
“…The incidence of post-renal transplant erythrocytosis is between 5% and 20% and is decreasing (Kiberd, 2009). PTE also occurs in approximately 1% of patients after haematopoetic stem cell transplantation (HSCT) (Ahmed et al, 2011;Atilla et al, 2016) and after combined pancreatic-renal transplant, with a reported incidence of 16% (Guerra et al, 2010). Post-transplant erythrocytosis following renal transplantation is a benign, often self-limiting condition which typically develops within the first year following transplantation, although it can occur at 2-4 years (Charfeddine et al, 2008;Kiberd, 2009).…”
Section: Post-transplant Erythrocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the recent report by Atilla et al 1 showing posttransplant erythrocytosis (PTE) following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Because the small number of cases has limited the impact of their conclusion, we would like to present the clinical features of our adult patients who developed erythrocytosis after allo-HSCT.…”
Section: Erythrocytosis After Allogeneic Hematopoietic Stem Cell Tranmentioning
confidence: 99%
“…1 Interestingly, the primary diseases in the present study were only AA and MDS (RA), and no patients received chemotherapy before allo-HSCT.These results indicated that the mechanisms for development of PTE in allo-HSCT recipients likely differ from other transplant recipients, and some immunological mechanisms may affect PTE in allo-HSCT recipients. PTE following allo-HSCT is a rare complication, 1,4 and our small experience indicates the need for a larger series of patients to clarify the pathogenetic mechanisms of PTE in allo-HSCT recipients.…”
mentioning
confidence: 95%